Does CO2 Emission Have Any Link With the Change Democratic Conditions in ASEAN Countries? - Phrakhruopatnontakitti, Phrakhruopatnontakitti; Watthanabut, Busakorn; Jermsittiparsert, Kittisak (International Journal of Energy Economics and Policy, 2020)
The study which is among pioneering studies answer the question that does CO2 emission have any link with the Change democratic conditions in ASEAN Countries. Great challenge in the form of global environmental problem has been faced by human society. Policy agendas for each country are governed by the political institutions. The present study aims to investigate the association among the state of political institution, environmental emission, and development indicator while taking the impact of economic conditions such as free economy, fluctuating economy, deteriorated economy and improvised economy under consideration. The study has collected the data of 10 ASEAN countries over the period from 1979 to 2014. The Panel data methodology is employed to answer the question raised in study. The Fixed effect estimates indicate that, economic growth is in significant positive relationship with change in democratic situation emission. It is also evident that the CO2 emission is higher in fluctuating Asean economies with relatively weak democracy such as Indonesia and Thailand and negative in the improvised democracies such Singapore. The study is among the pioneering studies on the current issue. This study will provide a guideline in environmental policy implementation. Keywords: Carbon emissions, democratic conditions, ASEAN countries JEL Classifications: Q2, Q4 DOI: https://doi.org/10.32479/ijeep.9169